2014
DOI: 10.1155/2014/765840
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Salt-Drought Stress on Growth and Physiobiochemical Characteristics ofTamarix chinensisSeedlings

Abstract: The present study was designed to clarify the effects of salinity and water intercross stresses on the growth and physiobiochemical characteristics of Tamarix chinensis seedlings by pots culture under the artificial simulated conditions. The growth, activities of SOD, POD, and contents of MDA and osmotic adjusting substances of three years old seedlings of T. chinensis were studied under different salt-drought intercross stress. Results showed that the influence of salt stress on growth was greater than drough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 14 publications
2
20
0
Order By: Relevance
“…The O2 and H 2 O 2 content increases in the leaves and petals of Tagetes erecta under long-term salt stress (Garg and Bhandari 2016). Salt stress increases the MDA content and membrane permeability of Ammodendron bifolium, Gleditsia sinensis (Liu et al 2014), and G. uralensis plants (Pan et al 2006). These results are similar to those observed in the present study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The O2 and H 2 O 2 content increases in the leaves and petals of Tagetes erecta under long-term salt stress (Garg and Bhandari 2016). Salt stress increases the MDA content and membrane permeability of Ammodendron bifolium, Gleditsia sinensis (Liu et al 2014), and G. uralensis plants (Pan et al 2006). These results are similar to those observed in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…Ji et al (2009) found that MeJA treatment counteracts the negative effects of salt stress on the growth, chlorophyll content, leaf photosynthetic rate, leaf transpiration rate, and proline content of soybean plants grown in a hydroponic medium. MeJA induces the expression of pathogenesis-related proteins (PR), such as PR-1 and PR-10, and salt-stress responsive protein in the roots of rice plants to combat stress (Moons et al 1997). Furthermore, MeJA can affect the whole-plant resource allocation of nitrogen-and carbon-containing substrates under stress (Gómez et al 2010).…”
Section: mentioning
confidence: 99%
“…Tamarisk plants exist as shrubs or small trees that are naturally distributed in saline soils of Eurasia, the Mediterranean basin and northern and southwestern Africa (Marlin et al, 2017;Sanz Elorza et al, 2010). Tamarix chinensis Lour is one of the most highly salt-tolerant tree species that is well suited for investigating salt-stress-response genes (Liu et al, 2014). The high salt tolerance of tamarisk trees was shown by tolerance limit studies and on 340 mM (2% (m/v)) NaCl treatment for 1 week caused no physiological damage to T. chinensis (Wang et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the aerial part is often related to the root part [31]. Du Jardin [32] observed that proline increases tissue concentrations and the root-to-shoot transport of micronutrients.…”
Section: Discussionmentioning
confidence: 99%